Repeated muscle glycogen supercompensation with four days` recovery between exhaustive exercise - Doering, T. M.; Cox, G. R.; Areta, J. L.; Coffey, V. G. (Journal of Science and Medicine in Sport, 2019)
Objectives: To determine if a 4 d period of high carbohydrate intake can supercompensate muscle glycogen and exercise work capacity on back-to-back occasions. Design: Seven trained cyclists (6 male, VO2peak: 57±4mLkg-1min-1) completed a 9-d experimental period, consisting of three intermittent exhaustive cycling trials on days 1 (trial 1), 5 (trial 2) and 9 (trial 3). Following trial 1 cyclists were fed a high carbohydrate diet (˜10gkg-1day-1) for eight days to assess their capacity to repeatedly supercompensate muscle glycogen with 4 d recovery. Methods: A resting muscle biopsy was obtained prior to each trial consisting of 2min work intervals (90-60% peak power output) interspersed with 2min recovery (40% peak power output) repeated until exhaustion. Each 72-h period between trial days included two days of low volume cycling and a rest day. Resting muscle glycogen and total work completed was determined for each trial day. Results: Baseline muscle glycogen on day 1 (583.6±111.0mmolkg-1 dry mass) was supercompensated on day 5 (835.1±112.8mmolkg-1 dry mass; p=0.04, d=2.25) and again on day 9 (848.3±111.4mmolkg-1 dry mass; p=?0.01, d=2.38). Total cycling work capacity increased from trial 1 to trial 2 (+8.7±5.4kJkg-1; p=0.01; d=1.41); a large effect was observed in trial 3 compared to trial 1 (+6.4±6.8kJkg-1; p=0.10; d=1.10). Conclusions: A 4 d high carbohydrate feeding strategy is sufficient to repeatedly supercompensate muscle glycogen content following exhaustive exercise and results in enhanced work capacity.